2013
DOI: 10.1371/journal.ppat.1003584
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Screening of Human Targets of Viral microRNAs Reveals Functions Associated with Immune Evasion and Angiogenesis

Abstract: Kaposi's sarcoma (KS) is caused by infection with Kaposi's sarcoma-associated herpesvirus (KSHV). The virus expresses unique microRNAs (miRNAs), but the targets and functions of these miRNAs are not completely understood. In order to identify human targets of viral miRNAs, we measured protein expression changes caused by multiple KSHV miRNAs using pulsed stable labeling with amino acids in cell culture (pSILAC) in primary endothelial cells. This led to the identification of multiple human genes that are repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 56 publications
3
44
1
Order By: Relevance
“…1A). We note that previous data demonstrated miRNA mimics are not overrepresented in the RNA-induced silencing complex, as determined by argonaute immunoprecipitation experiments (23,24). The reduced expression of GADD45B suggested that this gene was directly targeted for repression by KSHV miRNAs.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…1A). We note that previous data demonstrated miRNA mimics are not overrepresented in the RNA-induced silencing complex, as determined by argonaute immunoprecipitation experiments (23,24). The reduced expression of GADD45B suggested that this gene was directly targeted for repression by KSHV miRNAs.…”
Section: Resultssupporting
confidence: 52%
“…We utilized our previously published data sets that investigated changes in human gene expression in response to KSHV infection or in separate assays with cells transfected with KSHV miRNA mimics. We focused on mRNA expression changes after KSHV infection (22) or after transfection of a pool of KSHV miRNAs (23) and found that the growth arrest and DNA-damage-inducible 45 beta (GADD45B) gene was the 9th most repressed gene out of 13,795 microarray probes when combining these two data sets (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, miRNAs were shown to be derived from 12 precursor miRNAs (pre-miRNAs) encoded by sequences in the latency locus of the KSHV genome 60 . These miRNAs can contribute to oncogenesis by modulating cell differentiation 60 , cytokine production, and immune receptor signaling 61 .…”
Section: Etiologic Agents and Pathogenesismentioning
confidence: 99%
“…Furthermore, some miRNA targets are repressed at the level of translation and display little or no change at the mRNA level. Recently, a report have shown that using proteomic screening has been successful to identify viral miRNA targets that would be missed looking at the mRNA level [39][40]. Ideally, it is best to search for gene expression changes when showing a gain or loss of a single miRNA function.…”
Section: Mirna Target Prediction Strategiesmentioning
confidence: 99%